Comparative Effectiveness of Ketamine Versus Electroconvulsive Therapy in Treatment-Resistant Major Depressive Disorder - Jalaluddin Rumi, Junaid Rasool, Farooq Sultan Muhammad Usman, Bhawna Devi, Syed Ahmed Mahmud, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This randomized, noninferiority trial evaluates the clinical efficacy, cognitive outcomes, andtolerability of intravenous ketamine versus electroconvulsive therapy (ECT) in 365 adults withnonpsychotic, treatment-resistant major depressive disorder